Relation of Wilms Tumsor 1 scores with the Age of Ovarian Carcinoma Patients (The Planet, 2024)
Introduction: Worldwide, ovarian carcinoma is the seventh most common cancer and the eighth leading cause of death among women. Several studies reported Wilms tumor 1 (WT1) score as a potential marker for differentiating ovarian serous carcinoma from endometrial serous carcinoma. Aim of the study: This study aimed to assess the relation of Wilms tumor 1 score with the age of ovarian carcinoma patients. Methods and materials: Between July 2019 and June 2021, a cross-sectional descriptive study occurred at two notable medical institutions in Bangladesh: Rajshahi Medical College Hospital (RMCH) in Rajshahi and Bangabandhu Sheikh Mujib Medical University (BSMMU) in Dhaka. The study encompassed 31 suspected ovarian carcinoma cases admitted to RMCH, later confirmed through histopathological analysis. Participants were selected using purposive sampling, and data analysis utilized Microsoft Excel and SPSS version 20.0.Results: In assessing the relation between WT1 scores and the age of the subject we observed that age groups of 51-60 years showed the maximum positive staining. Among 66.6% of them showed >50% (3+), 11.1% of them showed 11-50% (2+) and 11.1% of them showed 1-10% (1+) WT1 scores. Only 11.1% of them showed negative. The age group of 20-30 years showed the maximum negative staining. Only 16.6% of them showed WT1 scores 11-50% (2+). We did not find any significant relation between WT1 and age. (P=0.220.   Conclusion: There is not any significant relation between Wilms tumor 1 scores and age of ovarian carcinoma patients.
Keywords: Wilms tumor score; WT1 scores; Ovarian carcinoma; Serous; Endometrioid